Problem-based learning as a catalyzer for understanding the yellow books - Prilianto, Figo; Rizal Nurzain; Taufiqurrahman; Asep Nursobah (Jurnal Iman dan Spiritualitas, 2025)
This study provides a comprehensive analysis of the implementation of PBL into the learning of yellow books at PMDG Campus 4. The focus of the study includes the impact of PBL and pedagogical innovation in Islamic boarding schools, as well as potential challenges and effective implementation strategies. This study uses a case study method with a qualitative approach, where data is collected through observation, in-depth interviews, and document analysis. The research subjects consisted of teachers, grade XI students, and the implementing committee involved in the learning program. The results of the study indicate that the Panca Jiwa PMDG is aligned with the student-centred PBL approach, and the core principles of PBL can be applied, yielding potential benefits in the learning of yellow books. The program implementation includes constructive, collaborative, contextual and independent learning. The findings of this study indicate that the PBL model approach can not only deepen students' contextual understanding, but also develop 21st-century skills to face contemporary challenges by upholding Islamic values. Thus, the right and accurate strategy reduces the challenges faced in implementing the PBL model in the learning of yellow books.